Active Biohybrid Nanocomposite Films Made from Chitosan, ZnO Nanoparticles, and Stearic Acid: Optimization Study to Develop Antibacterial Films for Food Packaging Application - Suyatma, Nugraha Edhi; Gunawan, Sanjaya; Putri, Rani Yunia; Tara, Ahmed; Abbès, Fazilay; Hastati, Dwi Yuni; Abbès, Boussad (Materials, 2023)
Chitosan is a biopolymer with great potential as food packaging due to its ability to create a film without additives and its better mechanical and antibacterial qualities compared to other biopolymers. However, chitosan film still has limitations due to its high moisture sensitivity and limited flexibility. Incorporating ZnO nanoparticles (ZnO-NPs) and stearic acid (SA) into chitosan films was expected to improve tensile strength, water vapor barrier, and antibacterial capabilities. This study aims to find the optimal formula for biohybrid nanocomposite films composed of chitosan, ZnO-NPs, and SA. The full factorial design approach—4 × 2 with 3 replicates, i.e., two independent variables, namely %ZnO-NPs at 4 levels (0%, 0.5%, 1%, and 3%, w/w) and %SA at 2 levels (0% and 5%, w/w)—was utilized to optimize chitosan-based biohybrid nanocomposite films, with the primary interests being antibacterial activities, water vapor barrier, and tensile strength. The incorporation of ZnO-NPs into chitosan films could increase antibacterial activity, while SA decreased it. The addition of SA had a good effect only in decreasing water vapor transmission rate (WVTR) values but a detrimental effect on other film properties mentioned above. The incorporation of ZnO-NPs enhanced all functional packaging properties of interest. The suggested solution of the optimization study has been validated. As a result, the formula with the inclusion of 1% ZnO-NPs without SA is optimal for the fabrication of active antibacterial films with excellent multifunctional packaging capabilities.
Keywords: ZnO nanoparticles; antibacterial films; biohybrid nanocomposite films; chitosan film; food packaging; full factorial optimization